Rhetorical Move Structures and Linguistic Realizations of Abstracts in ICT Research Articles and Master’s Theses - Amnuai, Wirada (Connexion: Journal of Humanities and Social Sciences, 2019)
Genre analysis has been used to examine the organizational structures of academic and professional writing. The objectives of this paper are to illustrate how abstracts in two different corpora were organized and realized in terms of functional meaning and also to investigate their grammatical features. Two sets of data were collected and analyzed using Hyland’s (2000) model. Differences were found in the frequency of occurrence of Introduction and Conclusion moves. Voice usage in the two corpora was clearly different. The findings provide insightful knowledge of rhetorical patterns and the use of lexico-grammatical features in each move in the abstracts. It is expected that the findings will assist novice writers or graduate students, particularly those in the field of information and communication technology in organizing their academic abstracts.